The impacts of decentralisation on forests and forest-dependent communities in Malinau district, East Kalimantan - Barr, C.; Wollenberg, Eva Karoline; Limberg, G.; Anau, N.; Iwan, R.; Sudana, I.M.; Moeliono, M.; Djogo, T. (Center for International Forestry Research, 2001)
Malinau District, established through partition in 1999, is the largest district in East Kalimantan and contains some of its largest tracts of forest. With decentralization, the district has sought to generate revenues from its forests, but these efforts have been handicapped by a concurrent lack of institutional capacities to manage rapid forest exploitation and conflicts over claims. Timber extraction and utilization permits (Izin Pemungutan dan Pemanfaatan Kayu or IPPK) have been the main instrument for revenue generation, with 39 IPPK covering 56,000 ha. expected to generate revenues equivalent to roughly nine times the district ’s 2000 budget. The IPPKs have enabled local entrepreneurs and communities to gain access to forest land and benefits previously controlled by centrally allocated concessions, however conflict has increased significantly where IPPK ’s overlapped with concessions and where IPPKs did not fulfill contractual obligations to communities. Overlapping adat or customary-based claims to land have fueled further conflict. While districts now enjoy more control and economic benefits from forests, there is a high risk of reconcentration of power at the district level, especially as government officials lack accountability to villagers and communities still lack secure legal rights to resources.